Effect of Reducing Sperm Number Per Insemination on Post Thaw Semen Quality and Fertility in Crossbred Cows - Kamboj, Prateek; Kumar, Ajeet; Honparkhe, Mrigank; Kaur, Simarjeet (The Indian Journal of Animal Reproduction, 2025)
The present study was carried out to evaluate the impact of using lower sperm concentrations (10 and 15 million per straw) on post-thaw semen quality and conception rates in cows, in comparison to the standard 20 million dose. Frozen semen from fertile crossbred bulls was processed into three concentrations—20M, 15M, and 10M sperm/straw and assessed using Computer-Assisted Sperm Analysis (CASA). Parameters such as total motility, progressive motility, and sperm kinematics were recorded. Additional evaluations included viability, acrosomal integrity and mitochondrial mem brane potential. A fertility trial was conducted on 75 estrus-synchronized cows divided into three groups of 25 each, corresponding to the three sperm concentrations. Artificial insemination was performed following ovsynch protocol. Conception was confirmed 60 days post AI by per-rectal palpation. CASA analysis of semen showed no significant difference (p>0.05) in motility and kinematic parameters across the three sperm concentrations. In cattle, the highest conception rate (48%) was found with 20M followed by 44% in 10M and 40% in 15M group. Reducing sperm concen tration to 15 and 10 million/straw had no significant effect on conception rate in cows. The findings in present study indicated that there is potential scope of using reduced sperm concentrations per insemination without much decline in CR in cows.